If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6x + -5) + 15x = 0 Reorder the terms: 3(-5 + 6x) + 15x = 0 (-5 * 3 + 6x * 3) + 15x = 0 (-15 + 18x) + 15x = 0 Combine like terms: 18x + 15x = 33x -15 + 33x = 0 Solving -15 + 33x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 33x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 33x = 0 + 15 33x = 0 + 15 Combine like terms: 0 + 15 = 15 33x = 15 Divide each side by '33'. x = 0.4545454545 Simplifying x = 0.4545454545
| F(x)=x^3-7x^2+24x-18 | | 2*x+0.5x+0.25x+1=100 | | F(x)=x^3+24x^2+7x-18 | | 584000= | | 3n^4-6n^2+9n=0 | | (1)4x+2=5 | | Y=-1x-(4) | | (3x+5)*2x=25 | | x-10=180 | | 3x+5x+2x+5=180 | | (X^2)-2XY=16 | | f(x)=8x^5+4x^4-4 | | 1(2+5x)=5 | | 7x^2-48a+64=0 | | ^24/3 | | -x-6=-6 | | n^2+7n+30=0 | | 523x=523x | | x+(3-2)=9 | | X-6=18-3x | | 9-x=25 | | 5y-1=3y+13 | | 7/12x-7/6x^2 | | 117=2x^2+7+61-x^2 | | 6y-24=12 | | 7n+21+n=37 | | 5x=65+x | | 6-(x+4)=12 | | 6y+4x=20 | | (3z-1)-(z+2)=15 | | 1.75x+0.65=10 | | 1.75-0.65x=10 |